Future Needs and Current Situation of Higher Education Competences in the Spanish Context - Astigarraga, Eugenio (2018)
This article aims to analyze and reflect on: (a) the role that competences–as a defining component of work activity and occupation in the coming decades—have in a hyper‑technological and globalized society; (b) the incorporation that is taking place in Spain of Skills-Based Training in Higher Education (both in professional training and in university studies); and (c) the conditioning factors and challenges that Higher Education faces in the immediate future in relation to competences. The technological factor—from robotization to artificial intelligence—together with demographic, social, and economic factors confirm the importance of cross-sectional competences in the careers of the future. Faced with this demand, it can be seen that the Higher Education is currently in the process of adopting competences as the axis of training. While the curricula have already been defined on the basis of competences, an advancement in methodological change is still required (through active methodologies), as well as in evaluation (considering learning results) so that the insertion of competences in Professional Training and in the university is complete.